The Kashima Operation: an Endoscopic Phonosurgery by LASER for Bilateral Vocal Cord Palsy – a case report - M. Alamgir Chowdhury; Farid Hossain Chowdhury; Khaled Bin Shahabuddin; A. B. M. Tofazzal Hossain; Shaila Kabir (Universiti Malaysia Sabah, 2021)
Complete or partial restriction of the vocal cords usually occurs due to cancer, neurologic causes or mechanical causes like huge neck mass, trauma to the neck, viral infection, and sometimes iatrogenic during surgery. Bilateral vocal cord palsy is a severe condition that can lead to significant problems in breathing, speaking, and swallowing. If any patient presents with stridor, it requires urgent surgical airway management followed by specific treatment. A case of viral bilateral abductor vocal cord palsy in a 41-year-old female is reported here. The patient presented with stridor, and immediate tracheostomy was done. The stridor developed first 3 months earlier followed by cold and fever for a week. The stridor worsened gradually and leads to a state of commencing immediate tracheostomy. There was no history of trauma to the neck or any neck surgery. All basic laboratory blood test was within the normal limit. The laryngoscopic examination showed both vocal cords were immobile and almost median position with a small gap at the posterior commissure. Chest and neck plain X-ray along with computed tomography scan of neck was normal which ruled out the other causes of bilateral vocal cord palsy. The patient subsequently underwent successful left posterior cordectomy by laser, and decannulation of tracheostomy was done, known as Kashima operation